Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2002
DOI: 10.1145/503376.503388
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of expanding targets

Abstract: There exist several user interface widgets that dynamically grow in size in response to the user's focus of attention. Some of these, such as icons in toolbars, expand to facilitate their selection − allowing for a reduced initial size in an attempt to optimize screen space use. However, selection performance may be degraded by this decreased initial widget size. We describe an experiment which explores the effects of varying parameters of expansion techniques in a selection task. Our results suggest that Fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 11 publications
0
87
0
1
Order By: Relevance
“…PA is one of many techniques that influence the motor-space through which the device travels during target acquisition: High gain reduces the motor distance during ballistic movement, and low gain increases the motor size of the target during corrective action. Other successful examples of motor-space adaptation include McGuffin and Balakrishnan's (2002) expanding targets; Grossman and Balakrishnan's (2005) bubble cursor; and Blanch, Guiard, and Beaudouin-Lafon's (2004) semantic pointing, all of which dynamically adjust motorspace to reduce the target distance, increase the width, or both. These techniques, fully reviewed in Balakrishnan (2004), are all target oriented: The CD gain or the target/cursor area is dynamically adjusted as a result of the cursor's proximity to the target.…”
Section: Dynamic Gain: Pamentioning
confidence: 99%
“…PA is one of many techniques that influence the motor-space through which the device travels during target acquisition: High gain reduces the motor distance during ballistic movement, and low gain increases the motor size of the target during corrective action. Other successful examples of motor-space adaptation include McGuffin and Balakrishnan's (2002) expanding targets; Grossman and Balakrishnan's (2005) bubble cursor; and Blanch, Guiard, and Beaudouin-Lafon's (2004) semantic pointing, all of which dynamically adjust motorspace to reduce the target distance, increase the width, or both. These techniques, fully reviewed in Balakrishnan (2004), are all target oriented: The CD gain or the target/cursor area is dynamically adjusted as a result of the cursor's proximity to the target.…”
Section: Dynamic Gain: Pamentioning
confidence: 99%
“…Unlike target-oriented approaches such as [11] and [12], Adaptive Pointing does not need any knowledge of the displayed information or active elements. However, it can be easily combined with visual interaction techniques such as expanding targets [19] or Dragand-Pop [20], as well as hand-tremor compensations (e.g. Kalman filter) if further pointing and selection improvement is desired.…”
Section: Adaptive Pointingmentioning
confidence: 99%
“…However, the effective width can be increased either for the cursor (Grossman & Balakrishnan, 2005;Kabbash & Buxton, 1995;Worden et al, 1997) or the target (Cockburn & Brock, 2006;McGuffin & Balakrishnan, 2002;Zhai et al, 2003) to achieve the same effect. Most previous studies have shown the effectiveness of their proposal only for single isolated target (McGuffin & Balakrishnan, 2002;Zhai et al, 2003), while they have not been shown to work well when multiple targets are present in close proximity (Cockburn & Brock, 2006;Guiard et al 2004;McGuffin & Balakrishnan, 2002;Zhai et al, 2003). The state of the art in this category is Bubble Cursor (Grossman & Balakrishnan, 2005), a mouse-based technique that allows selection of discrete targets by using a Voronoi diagram to associate void space with nearby targets.…”
Section: Previous Work On Selection Techniquesmentioning
confidence: 99%